Early clinical experience using the maxillary sinus antrostomy in "office rhinology"- currently dominated by balloon sinus dilation - Gary J Nishioka (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2018)
Background: Is there a role for the maxillary sinus anstrostomy (MSA) in office rhinology which currently is dominated by balloon dilation (BSD)? Introduction: The objective of this study was to retrospectively examine "office rhinology" patients who underwent in-office MSAs and identify relevant qualitative differences when compared to patients who underwent a maxillary BSD procedure, "independent" of clinical outcome or efficacy. Methods: A retrospective chart review was performed over a two-year interval and 5 patients were identified who underwent bilateral MSAs (10 sides total) as an office rhinology procedure for CRS without nasal polyps refractory to medical management with paranasal sinus CT scans showing persistent maxillary sinus radiographic changes. All patients underwent concomitant anterior ethmoidectomies with no other procedures performed, and were followed for a minimum of 4 months. A randomly selected cohort of patients who underwent office maxillary BSD procedures and partial anterior ethmoidectomies were used as a historical reference.  Results: 1) MSAs were easily performed and no intraoperative or postoperative complications were encountered. All patients could return to light activity within 48 hrs. 2) Removal of the uncinate process with the MSA provided superior visualization and access to the anterior ethmoid sinuses compared to the maxillary BSD patients. 3) The intact and often medialized uncinate process in maxillary BSD patients made examination of the maxillary sinus dilation site very difficult postoperatively, even with very angled endoscopes. In MSA patients endoscopic inspection of the antrostomy and sinus was very easy. 4) Removal of the uncinate process with the MSA procedure permited easy instrument access into the maxillary sinus if needed. In maxillary BSD patients instrument access into the maxillary sinus was essentially impossible.